Religious Passions and Prayer Channeling Divine Disclosure: The Testimony of the Fourth-Century Syrian Fathers - Miklós Vassányi (Religions)
In this paper, I investigate what role religious emotions, passions, and prayer may play in what may be called the religion of the heart in early Syrian theology, especially in the several works of ’Aphrahaṭ, Saint Ephrem, and the anonymous collection titled the Book of Steps, all from the fourth century. In the original Syriac sources, one may see how in this vast corpus, religious emotions and prayer act as a corridor channeling the believer’s striving for the disclosure of the mysteries surrounding God. It will also be shown that while these sources advocate in unison for the heart’s function in connecting the believer with God, their respective interpretive theological contexts are different. These points are substantiated by virtue of a number of citations from the original texts.